Elemental cellular contents of Rhodomonas salina and Oxyrrhis marina, and respiration rate and total lipids of O. marina during a starvation experiment - Meunier, Cédric Léo; Haafke, Julia; Oppermann, Bettina; Boersma, Maarten; Malzahn, Arne (PANGAEA, 2021)
This dataset contains data on the cellular elemental contents (carbon, nitrogen and phosphorus) of the phytoplankton species Rhodomonas salina grown in nitrogen limited and phosphorus limited conditions. These two phytoplankton qualities were offered as food to the heterotrophic dinoflagellate Oxyrrhis marina. The resulting cellular elemental contents of the dinoflagellates are also included for a stavation period of up to 78 h, as well as the cellular lipid content and respiration rate of O. marina fed with nitrogen limited or phosphorus limited R. salina, before being starved for 24 h or up to 48 h, respectively. To highlight possible differences in the source of energy used by differently preconditioned O. marina, we determined total lipid content following Urzua and Anger (2011).
Keywords: Dinoflagellata; elemental stoichiometry; Laboratory experiment; N limitation; nutrient; P limitation; Starvation